2021
DOI: 10.3390/plants10061199
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Storage Distribution Characteristics of Vineyard Ecosystems in Hongsibu, Ningxia

Abstract: Given that the global winegrape planting area is 7.2×106 hm2, the potential for winegrape crop-mediated carbon capture and storage as an approach to reducing greenhouse gas emissions warranted further research. Herein, we employed an allometric model of various winegrape organs to assess biomass distributions, and we evaluated the carbon storage distribution characteristics associated with vineyard ecosystems in the Hongsibu District of Ningxia. We found that the total carbon storage of the Vitis vinifera ‘Cab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Increasing pyrolysis peak temperature significantly increased biochar TC content, probably due to volatilization losses of other elements, especially H and O, and confirmed results reported by Ippolito et al [46]. The average TC content in grapevine pruning residues was 44.5%, which is similar to other studies [49][50][51], where authors reported values from 44.1% to 47.8%. In biochar, the average TC content was 75.4%, which agrees with the results of other studies (73.5%) [50], while a recent study reported even lower TC content (69.4%) [52].…”
Section: Discussionsupporting
confidence: 89%
“…Increasing pyrolysis peak temperature significantly increased biochar TC content, probably due to volatilization losses of other elements, especially H and O, and confirmed results reported by Ippolito et al [46]. The average TC content in grapevine pruning residues was 44.5%, which is similar to other studies [49][50][51], where authors reported values from 44.1% to 47.8%. In biochar, the average TC content was 75.4%, which agrees with the results of other studies (73.5%) [50], while a recent study reported even lower TC content (69.4%) [52].…”
Section: Discussionsupporting
confidence: 89%
“…The site (37°61′N, 106°12′E; 1,350 m a.s.l.) is located in a hilly landscape (part of the Yellow River Basin, administratively belonging to Wuzhong, China) at an elevation of 1,240–1,450 m, in the Loess Plateau of China (Figure 3a) (Zhang et al., 2021). This area has a typical temperate continental arid climate with an annual average temperature of 9.2°C (maximum daily temperature of 29.7°C and minimum daily temperature of −14.2°C).…”
Section: Methodsmentioning
confidence: 99%
“…As vineyards are a potential source of carbon storage [164], with differences among vine ages [165] and grape varieties [166], soil microorganisms are of great importance in regulating organic carbon dynamics [167], as taxa such as Patescibacteria, Synergistetes, Chloroflexi, Actinobacteria, Deinococcus-Thermus, and Atribacteria can degrade organic carbon to produce organic acids [168].…”
Section: Carbon Storagementioning
confidence: 99%